MODEL SISTEM OTOMATISASI PENGISIAN ULANG AIR MINUM - Malluka, Marlin; Surjati, Indra (Universitas Tarumanagara, 2008)
Every people’s need for drinking water in fulfilling daily needs is very important to support their activities. Technology developments, a life style of people were changes rapidly. In the past time to get the ready-to-consume water they had to boil it first, but now a simply refill the gallon with water. With the change of life style of the people who consume refill water in gallon, then various drinking water refill depots emerge, however in reality the water volume is not equal in every refill. For the above reason, the design of a microcontroller-based drinking water refill automation system model. This instrument consists of two sections that are transmitter and receiver. This drinking water refill automation system instrument can operate in accordance with the desire and can perform the refilling with minimum liter volume of 1 liter meanwhile the maximum volume of 15 liters.